A Carbonic Anhydrase IX (CAIX)‐Anchored Rhenium(I) Photosensitizer Evokes Pyroptosis for Enhanced Anti‐Tumor Immunity. (23rd December 2021) - Su, Xuxian; Wang, Wen‐Jin; Cao, Qian; Zhang, Hang; Liu, Bin; Ling, Yuyi; Zhou, Xiaotong; Mao, Zong‐Wan
Abstract: An ideal cancer treatment should not only destroy primary tumors but also improve the immunogenicity of the tumor microenvironment to achieve a satisfactory anti‐tumor immune effect. We designed a carbonic anhydrase IX (CAIX)‐anchored rhenium(I) photosensitizer, named CA‐Re, that not only performs type‐I and type‐II photodynamic therapy (PDT) with high efficiency under hypoxia (nanomolar‐level phototoxicity), but also evokes gasdermin D (GSDMD) mediated pyroptotic cell death to effectively stimulate tumor immunogenicity. CA‐Re could disrupt and self‐report the loss of membrane integrity simultaneously. This promoted the maturation and antigen‐presenting ability of dendritic cells (DCs), and fully activated T cells dependent adaptive immune response in vivo, eventually eliminating distant tumors at the same time as destroying primary tumors. To the best of our knowledge, CA‐Re is the first metal complex‐based pyroptosis inducer. Abstract : A carbonic anhydrase IX (CAIX)‐anchored photosensitizer CA‐Re was developed. It is capable of inducing and self‐reporting membrane rupture upon irradiation, as well as evoking pyroptosis to activate anti‐tumor immunity.